Edukasi Gizi Seimbang dalam Upaya Pencegahan Masalah Gizi pada Siswa di Pesantren Muara Bantarkalong Cipatujah - Taufiq Firdaus Al-Ghifari Atmadja; Nur Arifah Qurota A’yunin; Nisatami Husnul (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
According to RISKESDAS 2018 data, the prevalence of undernutrition and obesity among adolescents in West Java is concerning. The prevalence of undernutrition and obesity at Pondok Pesantren Muara Bantarkalong in Tasikmalaya Regency is also notably high. This issue is related to imbalanced eating habits and a lack of nutritional understanding among students and food handlers. The situation is exacerbated by students' preference for unhealthy snacks from outside the pesantren over the provided meals. This initiative aims to empower through the Healthy and Nutritious School Program, focusing on increasing nutritional knowledge among students at the pesantren. The results of this study indicate a significant improvement in nutritional knowledge, with the average score increasing from 6.7 in the pre-test to 8.025 in the post-test. Thus, it can be concluded that there is a notable difference in students' knowledge before and after the educational intervention.